Nickel-free environment — dreams vs. reality: Everyday utilities as a source of nickel and cobalt for patients sensitized to these metals - Łańczak, Anna; Choręziak, Aneta; Płocka, Maria; Sadowska-Przytocka, Anna; Czarnecka-Operacz, Magdalena; Adamski, Zygmunt; Jenerowicz, Dorota (Journal of Medical Science, 2019)
Introduction. Frequent occurrence of elevated nickel levels in everyday items explains why allergic contact dermatitis to nickel is the most common in the general population. In Northern America and Europe, 20% of the general population suffers from contact dermatitis while 8.6% of patients suffering from contact dermatitis are allergic to nickel.Material and Methods. A group of 25 patients (24 females and 1 male) sensitized to nickel and cobalt on the basis of patch testing was analyzed during a 2-year-long period in Department of Dermatology Poznań University of Medical Sciences. Contact allergy to nickel and cobalt was confirmed with the positive result of patch test, conducted with the Polish Standard Series of chemotechnique.Results. An excessive nickel release was detected in over a quarter of the tested items, respectively in 7.5% of jewellery, 57.89% of clothing accessories, 56.89% of other utility goods, such as keys, telephones or stationery. Cobalt excessive release was found in 7.3% of tested items, respectively in none of jewellery and kitchen accessories, 25% of clothing accessories, 12.5% of other utility goods (keys, pens, pendants).Conclusions. In general, everyday-use items are not nickel-free and more legislation steps are necessary to provide it and prevent initial sensitization in future generations. Several articles of every-day use release nickel and cobalt above migration limits.
Keywords: nickel allergy; cobalt allergy; Nickel Directive